2017
DOI: 10.1155/2017/7653791
|View full text |Cite
|
Sign up to set email alerts
|

The Aroma Composition of Baby Ginger Paocai

Abstract: The purpose of this study was to analyze the volatile compounds in baby ginger paocai and the fresh baby ginger and identify the key aroma components that contribute to the flavor of baby ginger paocai. A total of 86 volatile compounds from the two baby ginger samples were quantified; these compounds were extracted by headspace solid-phase microextraction (HS-SPME) and analyzed by gas chromatography-mass spectrometry (GC-MS). The aroma composition of baby ginger paocai was different from that of fresh baby gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Of the fresh ginger, dry‐salting, brine‐pickling, and inoculation‐pickling, α ‐zingiberene was also the highest (3253.27, 2664.30, 2704.67, and 3220.23 ug/g, Table 3 ), which was in line with the findings of research by Luo et al. ( 2017 ) on the volatile components of ginger. α ‐Zingiberene is mainly spicy and has a fresh flavor, and the characteristic aroma of white ginger itself, and thus the highest content in fresh ginger.…”
Section: Rseults and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Of the fresh ginger, dry‐salting, brine‐pickling, and inoculation‐pickling, α ‐zingiberene was also the highest (3253.27, 2664.30, 2704.67, and 3220.23 ug/g, Table 3 ), which was in line with the findings of research by Luo et al. ( 2017 ) on the volatile components of ginger. α ‐Zingiberene is mainly spicy and has a fresh flavor, and the characteristic aroma of white ginger itself, and thus the highest content in fresh ginger.…”
Section: Rseults and Discussionsupporting
confidence: 89%
“…the findings of research byLuo et al (2017) on the volatile components of ginger. α-Zingiberene is mainly spicy and has a fresh flavor, and the characteristic aroma of white ginger itself, and thus the highest content in fresh ginger.…”
mentioning
confidence: 99%
“…Sample preparation and extraction of volatile compounds employed solid-phase microextraction (SPME) according to the methods described by Luo and Zhao with some minor modications. 17,18 A SPME sampler equipped with a 50/30 mm divinylbenzene/carboxen/polydimethylsiloxane ber (DVB/CAR/ PDMS) (Supelco Inc. Bellefonte, USA) was applied to extract the volatile compounds in PRP. Aliquots of 10.0 g of minced PRP were transferred into 20 mL gas-tight glass vessels (Agilent technologies, Santa Clara, USA).…”
Section: Extraction Of Volatile Compoundsmentioning
confidence: 99%
“…At present, there are some studies related to the flavor and microorganisms of homemade paocai and brine, among which many results show that there are differences and correlations between the flavor and microbial community of different varieties of homemade paocai during fermentation (Rao et al, 2020; Xu et al, 2021), but few studies focused on industrial paocai and brine. Furthermore, while there may be hundreds of volatile compounds in a food, only a fraction of them contribute to the aroma profile (Aceña et al, 2011), and current research on the aroma‐active compounds in paocai is very limited (Luo et al, 2017). Our previous research has identified the aroma and bacteria profiles of different varieties of mature industrial paocai (Zhao, Wei et al, 2021), and found that the aroma profiles of industrial paocai were determined by both raw materials and microbiome.…”
Section: Introductionmentioning
confidence: 99%